Getting our way : 500 years of adventure and intrigue, the inside story of British diplomacy - Meyer, Christopher (London : Weidenfeld & Nicolson, 2009)
We have no eternal allies and we have no perpetual enemies. Our interests are eternal and perpetual, and those interests it is our duty to follow' -Lord Palmerston, 1848 This is a highly informed insider's account of some of the 'honest men' as they sought, by fair means or foul, to get Britain its way in the world.
Donated By Rebecca Dipa Khan
Keywords: Diplomatic and consular service, British -- History; Great Britain -- Foreign relations